Emotional and social intelligence as drivers of transformational leadership: Implications for supportive learning environments among international students - Limbachia, Ankita Dipakkumar; Riswanto, Aura Lydia; Wang, Jue; Kim, Hak-Seon (Journal of International Students, 2026)
In the era of globalized higher education, emotionally and socially intelligent leadership is essential for cultivating inclusive environments. This study uses partial least squares structural equation modeling (PLS-SEM) on a sample of 306 international students in South Korea to investigate how emotional intelligence (EI) and social intelligence (SI) drive transformational leadership (TL) and a supportive learning environment (SE). The results demonstrate that both EI (β = 0.122, p = 0.027) and SI (β = 0.679, p < 0.001) are powerful predictors of TL, with SI exerting a dominant influence. Furthermore, TL serves as a critical driver of SE (β = 0.539, p < 0.001) and significantly mediates the impact of both types of intelligence on the student experience. These findings establish that social and emotional fluency are foundational requirements for effective leadership.